LOCAL CULTURE-BASED LEARNING MATERIALS FOR STRENGTHENING STUDENTS' CHARACTER EDUCATION: A MIXED-METHOD STUDY - Rita Oktavia; Khairil Hadi (Sensei International Journal of Education and Linguistic, 2024)
Character education remains a central concern in primary education because schools are expected not only to develop students' academic competence but also to cultivate responsibility, respect, honesty, cooperation, and environmental care. However, character education is often delivered through moral instruction, classroom rules, and abstract values that are weakly connected to students' cultural experiences. Local culture-based learning materials offer an alternative by embedding character values in familiar stories, traditions, community practices, local wisdom, and contextual classroom activities. This study aims to examine the effectiveness of local culture-based learning materials in strengthening students' character education in primary schools and to explore how students experience character learning through culturally relevant materials. The study employed a mixed-method design using a quasi-experimental pretest-posttest control group approach supported by classroom observations, teacher interviews, student interviews, and document analysis. The participants were 96 fifth-grade students divided into an experimental group and a control group. The experimental group used local culture-based learning materials for eight weeks, while the control group received conventional character education materials. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, normalized gain scores, and effect size analysis. Qualitative data were analyzed thematically. The findings showed that local culture-based learning materials significantly improved students' character education outcomes. Qualitative findings revealed that the materials strengthened character learning through cultural familiarity, moral reflection, role modelling, collaborative activities, and contextual value application. The study concludes that local culture-based learning materials can strengthen character education when values are embedded in meaningful cultural narratives and classroom practices.